In silico identification and characterization of a diverse subset of conserved microRNAs in bioenergy crop Arundo donax L. Issue 1 (December 2018) - Jike, Wuhe; Sablok, Gaurav; Bertorelle, Giorgio; Li, Mingai; Varotto, Claudio
Abstract MicroRNAs (miRNAs) are small non-coding RNA molecules involved in the post-transcriptional regulation of gene expression in plants.Arundo donax L. is a perennial C3 grass considered one of the most promising bioenergy crops. Despite its relevance, many fundamental aspects of its biology still remain to be elucidated. In the present study we carried out the firstin silico mining and tissue-specific characterization of microRNAs and their putative targets inA .donax . We identified a total of 141 miRNAs belonging to 14 families along with the corresponding primary miRNAs, precursor miRNAs and a total of 462 high-confidence predicted targets and novel target sites were validated by 5′-race. Gene Ontology functional annotation showed that miRNA targets are constituted mainly by transcription factors, but three of the newly validated targets are enzymes involved in novel functions like RNA editing, acyl lipid metabolism and post-Golgi trafficking. Folding variability of pre-miRNA loops and phylogenetic analyses indicate variable selective pressure acting on the different miRNA families. The set of miRNAs identified in this study will pave the road to further miRNA research inArundo donax and contribute towards a better understanding of miRNA-mediated gene regulatory processes in other bioenergy crops.